A Comparative Study of Supervised Machine Learning Algorithm - Sathiya, D; Sonia, S. V. Evangelin (International Journal of Computer Sciences and Engineering, 2018)
Machine Learning is a process which begins with observations of data to make better decisions of new data in future. Machine Learning algorithms divides as Supervised Machine Learning, Unsupervised Machine Learning, Semi- Supervised Machine Learning and Reinforcement Learning. In this paper, we focus on Supervised Machine Learning Algorithms especially its error rates. A Supervised learning algorithm analyses the training data and produces a classifier (conditional function), which can then be used for mapping test sets. We compare the various Supervised Machine Learning algorithms in terms of its error rates in this paper.